2017
DOI: 10.4082/kjfm.2017.38.2.51
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work Is Associated with Metabolic Syndrome in Young Female Korean Workers

Abstract: BackgroundShift work is associated with health problems, including metabolic syndrome. This study investigated the association between shift work and metabolic syndrome in young workers.MethodsA total of 3,317 subjects aged 20–40 years enrolled in the 2011–2012 Korean National Health and Nutrition Examination Survey were divided into shift and day workers. We conducted a cross-sectional study and calculated odds ratios using multivariate logistic regression analysis in order to examine the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
3
16
2
1
Order By: Relevance
“…Considering that young nurses mostly work on shifts, we confirmed the relationship between shift work and MetS while controlling for subjects’ age. In this study, daytime working nurses had a higher MetS risk than nurses working in shifts, which is different from the results of the prior studies [ 34 , 59 ]. The critical indicators of MetS of low HDL-cholesterol, and increased waist circumference (WC), could be related to lower physical activity [ 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Considering that young nurses mostly work on shifts, we confirmed the relationship between shift work and MetS while controlling for subjects’ age. In this study, daytime working nurses had a higher MetS risk than nurses working in shifts, which is different from the results of the prior studies [ 34 , 59 ]. The critical indicators of MetS of low HDL-cholesterol, and increased waist circumference (WC), could be related to lower physical activity [ 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It is a set of symptoms, namely hypertension, dyslipidemia, dysglycemia and abdominal obesity, which occur secondary to insulin resistance (2). Its prevalence is 20.2% in the United States (3), 30% in Brazil (4) and 10.7% in South Korea (5). A meta-analysis on a sample of 74,440 Iranians stated that its prevalence in Iran is 34.7% (6).…”
Section: Introductionmentioning
confidence: 99%
“…Shift work was associated with metabolic syndrome in female workers but not in male workers 8). The authors explained this discrepancy by a high prevalence of menstrual irregularity and high obesity rates in shift workers.…”
mentioning
confidence: 94%
“…In another cross-sectional study by Yu et al,8) an association between shift work and metabolic syndrome was demonstrated in young adults using data from the 2011–2012 KNHANES database. This study included 3,317 individuals ranging from 20 to 40 years of age.…”
mentioning
confidence: 95%
See 1 more Smart Citation